2011
DOI: 10.1384/jsa.18.26
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbon Contaminations on Electron-Induced Damage of SiO<sub>2</sub> Film Surface at Different Electron Primary Energies

Abstract: Dependence of the electron-induced damage of the clean and carbon-contaminated SiO 2 film surfaces during the Auger electron spectroscopy measurement was investigated under irradiation of electrons at different primary energies. The variation in the intensity of the Si-LVV elemental peak with the increase in the electron dose was measured and analyzed within the scheme of the two-step decomposition model [J. Surf. Sci. Soc. Jpn. 25, 212 (2004) (in Japanese)]. The results clearly revealed that the rate of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…From these figures, it is confirmed that the decomposition cross sections tend to be smaller for the SiO 2 film surface with a larger amount of carbon contaminations under the irradiation of primary electrons. Note that the order of magnitude of σ 1 and σ 2 is similar to those reported previously [9][10][11][12]15].…”
Section: Figsupporting
confidence: 87%
See 2 more Smart Citations
“…From these figures, it is confirmed that the decomposition cross sections tend to be smaller for the SiO 2 film surface with a larger amount of carbon contaminations under the irradiation of primary electrons. Note that the order of magnitude of σ 1 and σ 2 is similar to those reported previously [9][10][11][12]15].…”
Section: Figsupporting
confidence: 87%
“…16, it is found that the dependence of the electron-induced damage on the initial amount of carbon contaminations is significant for the lower beam current. Although the role played by carbon contaminations in the reduction of the electron-induced damage of SiO 2 is not clear at present, the carbon contamination layer is considered to behave as the protective capped layer for the decomposition of SiO 2 [1,15]. The carbon contaminations are desorbed with the increase in the electron dose probably by the oxidation by oxygen decomposed from SiO 2 .…”
Section: E Electron-induced Damage Of Sio2 Film Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 displays the AES spectrum acquired just after preparation of the film (top spectrum), then the spectra are recorded in the same measurement conditions after 7 min and next after 24 h of air exposure. One notices that upon air exposure most of the oxidation process of the silicene film (presence of SiO 2 signal, 82 eV [45][46][47], or Si suboxides [46,47]) has occurred within 7 min. However, even after 24 h in air, this 43 MLs silicene film remains largely intact, being oxidized only at its top Typically, the Si LVV signal reveals that the Si-Si bonds largely dominate over Si-O ones [46,47].…”
mentioning
confidence: 99%